Object clitics in Cypriot Greek children with SLI - Theodorou, Eleni; Grohmann, Kleanthes K. (My University, 2015)
This study investigates the production and placement of direct object clitic pronouns in children with specific language impairment (SLI). A total of 38 bilectal children were divided into four groups: two groups of children with SLI and two groups of age-matched typically developing children; 5-year-olds in the younger and 7-year-olds in the older groups. The goals of the study were (i) to investigate whether object clitics could serve as a clinical marker for Cypriot Greek-speaking children with SLI, (ii) to explore whether there are any quantitative and/or qualitative differences between typical language development and SLI, and (iii) to determine possible differences between the age groups. The design of the experiment aimed to shed some light on the question whether children with SLI exhibit difficulties with clitic production in the context assessed. The results reported here do not support the cross-linguistic finding that clitic production could serve as a clinical marker for SLI in Cypriot Greek. However, what seems to be at stake is clitic (mis)placement, and the findings provide some evidence that there is more than meets the eye concerning the theoretical discussion around the use of clitics in Greek Cypriot children’s language development.
Keywords: (Discrete) Bilectalism; Clitic placement; Diglossia; Elicitation production; Socio-syntax of development hypothesis; Specific language impairment (SLI)